Sectoral Analysis of Foreign Direct Investment and Economic Growth in Nigeria - Otuekong, Nsikak Otu (2009)
Foreign direct investment (FDI) is viewed as a major stimulus to economic growth in developing countries, yet its success varies by sectors. Thus, this study examines the relationships between sectoral FDI and economic growth in Nigeria using annual time series data from 1970 to 2006. In the empirical analysis, Augmented Dickey-Fuller and Phillip-Perron unit root test were employed to test for the stationarity of the data. The result of Johansen‟s cointegration test shows the existence of a long-run relationship between sectoral FDI and gross domestic product (GDP). Moreover, the existence of cointegration presumes the presence or absence of Granger causality, which however does not indicate the direction of causality between the variables; hence the short-term impact of sectoral FDI on sectoral output and GDP respectively was tested using Granger causality test. The result of the test reveals a short-run causal effect running either unidirectionally or bidirectionally among the variables, though there was also evidence of lack of any causal relationship among the variables also. Furthermore, two sectors manufacturing and processing as well as mining and quarrying accounted for substantial proportion of investment and therefore remains the dominant sector attracting FDI inflows in Nigeria. These findings imply that in the long-run, some sectoral FDI can be used to predict GDP. However, understanding the direction of causality between sectoral FDI and output as well as between sectoral FDI and GDP is crucial for formulating policies that will encourage investment in Nigeria.